7q-(q-3)=3q+3(q+1)

Simple and best practice solution for 7q-(q-3)=3q+3(q+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7q-(q-3)=3q+3(q+1) equation:


7q-(q-3)=3q+3(q+1)

We simplify the equation to the form, which is simple to understand
7q-(q-3)=3q+3(q+1)

Remove unnecessary parentheses
7q-1q+3=3q+3*(q+1)

Reorder the terms in parentheses
7q-1q+3=3q+(+3q+3)

Remove unnecessary parentheses
+7q-1q+3=+3q+3q+3

We move all terms containing q to the left and all other terms to the right.
+7q-1q-3q-3q=+3-3

We simplify left and right side of the equation.
q=0

0=0

This equation is an identity, so all real numbers are solutions.

See similar equations:

| 10ab+2ab^2-9ab= | | 64-7=295 | | -4(5-3y)=4y+12 | | -2(-9m-2-1)=27+10m | | 4t-t-6=2t-5 | | 10=-14-2y-4y | | 5(1-2x)+4x=12 | | 3(x)-12=24 | | (-8a^3b^3)(6ab^6)= | | 8-40/2 | | 18x+20y+15+14x-9y-2= | | X+5=-10+6-2-2x-3 | | [33-6x]=37 | | c-6=1-2 | | 1/4(12x-40)=2/9(27x+9) | | 1x=8x-6 | | 5-5x=6+2x | | 20=5(8x+6) | | [27-3x]=21 | | -8z+18=2(2z)-9 | | 6x-7y+11z= | | 9-x=-12 | | 0.14-0.02(x+2)=-0.02(1-x) | | 12=24-7x-5x | | 12-9(y+5)=-(1-5) | | 4(x+7)-15=-3 | | -3(x+6)-41=1-36 | | 5x-5=5x+45 | | -4(4u-8)+6u=6(u+5) | | 2x^2+24x+69=y | | -2n-4=8 | | z-16=-19 |

Equations solver categories